ANALISIS DAN PERANCANGAN JARINGAN MPLS VPN MENGGUNAKAN METODE FAILOVER LINK (Information Technology and Telematics, 2015)
Abstrak :~~ Bank BPD DIY as one of the regions need a network that can connecting HO (Head Office - Headquarters) and BO (Branch Office - Branch Office) which is spread over an area of D.I. Yogyakarta which is used to exchange data and information. According to the vision and mission as a provider of banking services, financial services and to promote regional economic development program, it is necessary that network connectivity must be stable and reliable. Nowadays, the existing network between the HO and the entire BO is connected, but there is a problem when an interruption occuring in the HO connection, then the whole BO cannot exchange the data and information. The purpose of this research is to design a network with MPLS-VPN-based by using the failover link, which is expected to overcome the problems that occur, the objective is to provide availability to the Bank BPD DIY network with backup link if the main link is down. Failover link is made to maintain the quality of connectivity and availability on the link BPD DIY so that the exchange of data and information between the HO BO optimally maintained. Keywords :  Failover, MPLS, Networking, VPN,